HIGH VALUE AGRICULTURE IN THE REPUBLIC OF MOLDOVA, COMPARATIVE ANALYSIS AND FEASIBILITY OF INVESTMENTS - Andrei ZBANCĂ; Sergiu PANUȚA; Virgiliu MOREI; Grigore BALTAG (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of Moldova’s integration into the international economic system requires a qualitative change of the current situation in the food sector. The globalization of the world economy and the technical – scientific progress provides new opportunities for increasing efficiency and upgrading production technologies for agricultural production. In Moldova this task can be achieved by targeting entrepreneurs towards crop diversification and export of agricultural products with high added value, for which there are profitable and modern markets. Currently, entrepreneurs focus on development of high-value agricultural sector, which provides the greatest profits and, due to this fact, could become an important source of increasing income in the rural sector. The aim of the research is a comparative analysis of cultivation of high value crops, and the result is to create an informational support that enables local entrepreneurs to select the correct crops based on the economic indicators and financial resources to invest argued. Information and research results were made under the Agricultural Competitiveness and Enterprise Development Project (ACED). The authors have developed annual financial models for each crop and perennial plantations were developed additional investment budgets. High value production (particularly fruit and vegetables) offers the highest profits and it has great to increase farmers’ incomes. For small and medium farms practicing commercial agriculture (HVA) is the solution for developing efficient and sustainable business in market economy.